The Juxtaposition of Natural Beauty and Ravages of War: Human Nature Relationship in Khaled Hussein's The Kite Runner - Acharya, Govinda Prasad (Humanities and Social Sciences Journal, 2024)
This study examines the representation and significance of nature in Khaled Hosseini’s The Kite Runner, highlighting the interconnectedness of humans and nonhumans beyond traditional hierarchical structures. Moreover, this study examines the intricate relationship between natural beauty and the devastation of war. Through a close textual analysis, the research examines how Hosseini juxtaposes serene landscapes with scenes of violence and destruction to underscore the emotional and psychological impact of conflict on both individuals and their environment. The paper argues that nature serves not only as a backdrop but also as a silent witness and occasional refuge. This paper explores in detail what sorts of ecological disasters have been imposed on Afghanistan by these cruel wars. This juxtaposition of natural beauty and the ravages of war is presented through the ecocritical lens, discussing poverty, cruelty, ethnic cleansing, suffering, and resilience that the Afghans underwent and endured in the novel. The study reveals the lasting human nature bond, the enduring capacity of human beings in all situations to which human beings are bound. This study will ultimately convey the message that homo-sapiens are heading to become human creatures through their prejudices, insanity, and cruelty, and war is their favored method.